The Impact of Open-Book Testing Approach on the Achievement of EFL Sudanese Students at Tertiary Level (Journal of Faculty of Education, 2023)
This study sought to investigate the impact of open-book assessment on third year students’ English language achievement at University level. The importance of this study stems from the need for adopting many different methods of assessments which are valid and reliable to ensure that these programmers can achieve their objectives and educational aims. This study used the qualitative method for data collection. Two tools were used, an experiment and a questionnaire to collect data to answer the research questions addressing the problem. The sample of 40 students was selected and divided into two groups, an experimental group and a control group, 20 students in each group. Data was collected from the students through a questionnaire. The results of the study showed that the group who was subjected to open-book assessment out-performed their peers in the control group. In addition, analysis of variance tests showed that open-book assessment is more effective in enhancing higher-order skills. The result of Chi Square test reveals that implementing open-book assessment raises a number of challenges and obstacles on part of the students. It is recommended that the students should learn how to prepare for open-book examination which need not be used solely, but may be supplemented by closed-book examination.
Keywords: : open- and closed- book assessment; critical thinking; achievement